Flexible Model on Special Education Services in Inclusive Setting Elementary School - Imas Diana Aprilia (Department of Special Education, 2017)
This research intends to study the implementation of inclusive education in elementary schools in the district of Bandung in order to create a model for special education services in regular schools. The results of the implementation analysis combined with the results of the literature study used as a basis to design the model of special education services in inclusion settings. The main finding of this study is